Implementasi Perencanaan Keuangan Desa pada Gampong-Gampong di Kabupaten Aceh Selatan - Aijeal Mushawir (Institut Pemerintahan Dalam Negeri (IPDN), 2021)
Gampong financial planning is one indicator to see the success or failure of financial management and administration of governance of a village. This study aims to determine the implementation of gampong financial planning in the gampong in Mukim Pisang Baru - Labuhanhaji Subdistrict, to find out the obstacles or obstacles faced by the Gampong Government in the gampong financial planning process, and to find out the efforts made by the sub-district and gampong governments in overcoming obstacles in the gampong financial planning process that is. The research method used is qualitative research with descriptive methods, by seeking understanding obtained from data and facts in the field. Sources of person data used include the Government apparatus of the Labuhanhaji District, Gampong Dalam Government apparatus, Gampong Kota Palak, Gampong Cacang, Gampong Pisang, Gampong tengah Pisang, Gampong Hulu Pisang, and Gampong People’s Consultative Body (Tuha Peut). The results showed that the gampong in Mukim Pisang Baru - Labuhanhaji Subdistrict had attempted to carry out gampong financial planning, especially the preparation of the Gampong Revenue and Expenditure Budget based on the latest regulation namely Permendagri Number 20 Year 2018 concerning Village Financial Management. In the first years, obstacles were found because this regulation was urgent and important. However, as the budget year progresses and the guidance given to the gampong’s government. There are no more complicated problems found related to the implementation of the Permendagri Number 20 Year 2018 concerning Village Financial Management in Mukim Pisang Baru – Labuhanhaji Subdistrict. The Labuhanhaji District Government have made various efforts to overcome these obstacles so that in the future gampong financial management, especially gampong financial planning in Mukim Pisang Baru – Labuhanhaji Subdistrict, can be done better by referring to existing regulations and provisions.